DE SITTER METRIC WITH MAGNETIC FIELD - Korkina, M. P.; Kazemir, V. S. (Одеські астрономічні публікації, 2007)
De Sitter model with magnetic field was considered. The exact solution was obtained. The properties of the model in comparison with empty de Sitter model were analyzed.